Implementing the General Education Development (GED) Program in First Nations Communities: Struggles for Power (Alberta Journal of Educational Research, 2016)
This paper describes an ethnographic case study of eleven First Nations adult learners in a Northern Ontario community attempting to earn secondary school equivalency through the General Education Development (GED) program. The paper maintains a focus on the power differentials at work in both the learners' prior educational endeavours and their experiences while working inside of the GED program. Based on the data, we argue that, despite appearances to the contrary, First Nations learners are subjected to a system of education that is failing to empower those learners to take advantage of educational opportunities that are available in mainstream Canadian society.Cet article décrit une étude ethnographique de cas auprès de onze apprenants adultes autochtones qui tentent, dans une communauté du Nord de l’Ontario, d’obtenir une équivalence d’études secondaires par des cours de formation générale (GED). Plus précisément, l’article porte sur les écarts systémiques de pouvoir qui entrent en ligne de compte tant dans les études préalables des apprenants que dans leurs expériences avec le programme GED. En s’appuyant sur les données, nous affirmons que, même si les apparences peuvent laisser supposer le contraire, les apprenants autochtones sont soumis à un système d’éducation qui ne réussit pas à les doter des compétences nécessaires pour saisir les possibilités éducatives offertes par la société canadienne.